2019
DOI: 10.1007/s13205-019-1719-3
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of water-deficit stress-responsive α-expansin 1 (EXPA1) gene from Saccharum complex

Abstract: In this study, full-length (1282-1330 bp) α-expansin 1 (EXPA1) gene from three different accessions belonging to Saccharum complex (Saccharum officinarum-SoEXPA1, Erianthus arundinaceus-EaEXPA1, and Saccharum spp. hybrid-ShEXPA1) was isolated using RAGE technique and characterized. The intronic and coding regions of isolated expansin genes ranged between 526-568 and 756-762 bp, respectively. An open reading frame encoding a polypeptide of 252 amino acids was obtained from S. officinarum and commercial sugarcan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…The transcripts of many α-expansins are up-regulated under abiotic stress (Marowa et al, 2016 ; Tenhaken, 2015 ). Accordingly, genetic approaches have shown that enhanced expansin expression might contribute to stress tolerance to drought (Chen et al, 2016 ; Hao et al, 2017 ; Liu et al, 2019 ; Narayan et al, 2019 ; Yang et al, 2020 ), high salinity (Chen et al, 2017 ; 2018a ; Hao et al, 2017 ; Lu et al, 2013 ; Yan et al, 2014 ; Zhang et al, 2019b ), heat (Xu et al, 2007 ; 2014 ), cold (Peng et al, 2019 ; Zhang et al, 2018a ), oxidative (Chen et al, 2018b ) and heavy metal (cadmium) stress (Ren et al, 2018 ; Zhang et al, 2018b ). Moreover, Han et al ( 2012 ; 2015 ) described that overexpression of -expansin TaEXPB23 also enhanced tolerance to oxidative and salt stress, similar to the -expansins ZmEXPB6 and ZmEXPB8 studied by Geilfus et al ( 2015 ) and Wu et al ( 2001 ) respectively.…”
Section: Expansins Under Abiotic Stressmentioning
confidence: 99%
“…The transcripts of many α-expansins are up-regulated under abiotic stress (Marowa et al, 2016 ; Tenhaken, 2015 ). Accordingly, genetic approaches have shown that enhanced expansin expression might contribute to stress tolerance to drought (Chen et al, 2016 ; Hao et al, 2017 ; Liu et al, 2019 ; Narayan et al, 2019 ; Yang et al, 2020 ), high salinity (Chen et al, 2017 ; 2018a ; Hao et al, 2017 ; Lu et al, 2013 ; Yan et al, 2014 ; Zhang et al, 2019b ), heat (Xu et al, 2007 ; 2014 ), cold (Peng et al, 2019 ; Zhang et al, 2018a ), oxidative (Chen et al, 2018b ) and heavy metal (cadmium) stress (Ren et al, 2018 ; Zhang et al, 2018b ). Moreover, Han et al ( 2012 ; 2015 ) described that overexpression of -expansin TaEXPB23 also enhanced tolerance to oxidative and salt stress, similar to the -expansins ZmEXPB6 and ZmEXPB8 studied by Geilfus et al ( 2015 ) and Wu et al ( 2001 ) respectively.…”
Section: Expansins Under Abiotic Stressmentioning
confidence: 99%
“…The members of the expansin family were significantly over-represented in the hypergeometric annotation tests as well as the differential expression analysis, which identified nine different transcript annotations of expansins as well as other canonical floral induction integrators. As culms produced new vertical growth, the upregulation of multiple expansin family members validated their role in the reproductive process of Tripidium [ 71 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a perspective of understanding the role of NF-YB2 subunit in drought and salinity stress response, NF-YB2 from E. arundinaceus, a wild relative of Saccharum, a known source of drought and salinity stress tolerance (Augustine et al 2015b;Valarmathi et al 2018;Manoj et al 2019;Ashwin Narayan et al 2019) and commercial Saccharum hybrid Co 86032 was isolated and characterized. The isolated EaNF-YB2 and ShNF-YB2, each of 543 bp, predicted to encode a protein of 180 amino acid residues which shared identity of 97% with S. bicolor NF-YB2 and 93% identity with Z. mays NF-YB2 with 100% query coverage.…”
Section: Discussionmentioning
confidence: 99%
“…A successful hybridization between Saccharum spp hybrids and Erianthus species, and the presence of Erianthus chromosomes in intergeneric hybrids have been reported (D'Hont et al 1995;Piperidis et al 2000Piperidis et al , 2010Nair et al 2017;Premachandran et al 2017). E. arundinaceus is well known for its tolerance to abiotic stresses (Ram et al 2001;Augustine et al2015a, b, c;Anunanthini et al 2019;Ashwin Narayan et al 2019;Deng et al 2019;Manoj et al 2019) and has become a powerful genetic resource for the genetic improvement of the sugarcane varieties. It has been reported that drought and salinity induce many stress-responsive mechanisms regulated by various genes which include genes encoding transcription factors (TFs).…”
Section: Introductionmentioning
confidence: 99%